APPLICATION OF ACACIA TANNINS IN ELASTIC LEATHER MATERIALS PRODUCTION TECHNOLOGY - DANYLKOVYCH, Anatoliy; SANGINOVA, Olga (Herald of Khmelnytskyi National University. Technical sciences, 2023)
An IR-spectroscopic study of the interaction of collagen with blackwood acacia (acacia melanoxylon) tannins and its use for tanning and filling semi-finished leather products in the production of elastic leathers for shoe uppers was conducted. The analysis of IR spectra of the interaction of the chrome tanning collagen products dermis with the acacia extract tannins can indicate the intermolecular ionic bonds formation and a hydrogen bonds dense network building-up with the amino groups of collagen and phenolic and carbonyl groups of the plant extract tannins. The following reagents were used for the semi-finished product tanning: sodium chloride TU 9192-069-00200009527-98, formic and sulfuric acids according to DSTU GOST 1706-78 and DSTU GOST 2184:2018, and sodium carbonate ISO 6353-2-83. Blackwood acacia extract together with the synthesis product of 2-naphtholsulfonic acid with dioxydiphenylsulfone as synthetic tanning agent BNS TU 17-06-165-89 were used to fill the tanned semi-finished product. The application of BNS TU 17-06-165-89 syntan in the process of finishing and filling of chrome tanned semi-finished leather product after catting it into thin slices with a thickness of 1.4 mm together with acacia extract tannins ensures an increase in its diffusion into the structure and provides a process duration reduction. The use of acacia extract tannins in the production technology of elastic hides makes it possible to obtain a filled-greased semi-finished product with increased physical and chemical properties: porosity, volumetric yield, air permeability by 21, 37, 86%, respectively, compared to the chrome tanning semi-finished product. The obtained results give the grounds for recommendation the use of acacia extract tannins in the wide range of elastic leathers production technologies.